Passing the Temporal Borders Across the Selves: Examining the Association Between Time Perspectives, Consideration of Future Consequences and Future Self-Continuity - Akman Direkçi, Emine; Boyacıoğlu, İnci (Border Crossing, 2024)
In the complex landscape of human decision-making and behaviour, several psychological constructs play a crucial role in shaping people’s attitudes towards the past, present, and future. This study examines the interplay between how we perceive our future selves, our consideration of future consequences, and our general time perspectives aiming to deepen our understanding of temporal cognition and its implications for human behavior. The study explored how these factors interact and potentially influence our decisions and behaviour. Through a web survey questionnaire data was collected from the university students. Quantitative analyses explored the associations between individuals’ levels of consideration of future consequences, future self-continuity, and their temporal orientations as measured by Zimbardo’s Time Perspective Inventory. Results of the study suggests complex associations between these constructs, with individuals’ time perspectives and future self-continuity exerting significant influences on consideration of future consequences. By understanding these relationships, gained valuable insights into how individuals make decisions that bridge the gap between their present and future selves and its association with temporal orientations. We discussed implications of the present study on the consideration of future consequences and it provides insights for future investigations.